2020
DOI: 10.1177/0971685820947334
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Effectiveness and Psychological Well-being: The Role of Workplace Spirituality

Abstract: The purpose of this article is to examine the relationship of leadership effectiveness and psychological well-being with the work outcomes of intention to quit, job involvement and organization-based self-esteem (OBSE), and whether workplace spirituality plays a role in mediating the associations of leadership effectiveness and psychological well-being with work outcomes. The study is cross-sectional and non-experimental. Data were obtained from 630 information technology (IT) employees from South India, adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…It contributes to our existing knowledge in a variety of ways (Riasudeen, 2021).To begin, it advances LED product research by considering changes in customer behavior due to lower LED light prices now than when the earlier literature was published. Second, it compares the TPB framework's validity and relevance to prior research across various demographics and periods.…”
Section: Introductionmentioning
confidence: 99%
“…It contributes to our existing knowledge in a variety of ways (Riasudeen, 2021).To begin, it advances LED product research by considering changes in customer behavior due to lower LED light prices now than when the earlier literature was published. Second, it compares the TPB framework's validity and relevance to prior research across various demographics and periods.…”
Section: Introductionmentioning
confidence: 99%
“…• Develop manager's skills: line managers must be suitably skilled for remote working to be beneficial for employees. Managers need to develop skills to manage remote workers through easy communication, monitoring and motivating them as effectively as they would if they were at the office [35].…”
Section: Support Strategies For Remote and Hybrid Workersmentioning
confidence: 99%
“…• Learning and development: Research by Riasudeen and Singh [35] on employee engagement revealed that employees need and want to feel valued, supported and to perform meaningful work. An organisational culture that values its employees and supports their growth and development should thus be evident.…”
Section: Advancing the Psychological Well-being Of Remote And Hybrid ...mentioning
confidence: 99%
“…The role of HR practices is noteworthy in assessing employee work engagement (Ha and Lo, 2018;Ybema et al, 2020). It is found that HR practices impact directly employee behavior and engage the employee in work-related tasks effectively (Goswami et al, 2021;Riasudeen and Singh, 2021;Teo et al, 2020;Ybema et al, 2020). Recently authors like Ybema et al (2020) have revealed a strong connection between HR practices and employee work engagement.…”
Section: Human Resource Compensation and Trainingmentioning
confidence: 99%